Analysis of dog bite surveillance data, Volta Region, Ghana, 2020 - Gborie, Sahr Raymond; Issahaku, Gyesi Razak; Bonful, Harriet Affran; Bandoh, Delia Akosuah; Squire, James; Ameme, Donne Kofi; Kenu, Ernest (Frontiers in Tropical Diseases, 2023)
Introduction Dog bite is the second most common injury sustained by humans after snake bites, and it is amongst the top 12 causes of non-fatal injuries worldwide. Globally, 59,000 human deaths occur annually due to rabies, and 95% of these deaths occur in Asia and Africa. Dog bites remained a public health concern in Ghana, with three out of every 1000 incidence resulting in human rabies. Analysis of the surveillance data is key in understanding the burden of dog bites in the Volta region. This study describes the epidemiology of dog bites in the Volta Region, Ghana, to inform policy on prevention and control. Methods We conducted a descriptive analysis of secondary data on dog bites. We obtained aggregate data from 2015 to 2019 from the District Health Management Information System (DHMIS). Variables extracted were gender, age, and location. Data were entered into a Microsoft Excel cleaned, reviewed, and analyzed. We used descriptive statistics to summarize results into frequency and proportion and displayed results in tables, graphs, and maps. Results During the study period, 4737 dog bite cases were identified from a population of 1,907,529 (incidence of 248 per 100,000). Twelve (0.25%) humans were confirmed for rabies with a 100% case fatality rate. Males accounted for 2455 (51.8%) of dog bite cases. The age group between 10 and 19 years (21.9%) was most affected. About 35.0% (1640/4737) were administered with the anti-rabies vaccine, and 25.3% (1200/4737) were administered anti-tetanus toxoid. Keta district (550 per 100000) reported the highest incidence of dog bites. Dog bite cases were highest in the third and fourth quarters of 2016 and the first quarter of 2017. Conclusion The incidence of dog bites and rabies was high in the Volta region. Children and adolescents were mostly affected. There was a low coverage rate of anti-rabies vaccine and anti-tetanus toxoids usage. We recommended that the Regional Health Directorates and the Regional Veterinary Department develop robust strategies to control stray or free-roaming dogs in the Volta region.